1973
DOI: 10.1001/archinte.1973.00320110093014
|View full text |Cite
|
Sign up to set email alerts
|

Methylguanidine in Uremia

Abstract: Methylguanidine (MG) has been demonstrated to be elevated in serum of uremic patients and its retention, per unit of serum creatinine concentration, to be higher in the anuric patients than in those with urine output exceeding 400 ml/day. The metabolic production of MG has been found to be increased in renal failure and correlated with the serum creatinine concentration, and its renal tubular excretion to be also elevated.In ten dogs submitted to ligature of the ureters, higher concentrations of MG were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 13 publications
1
52
1
Order By: Relevance
“…Thus (about 120nM) (19). However, the levels of MG and GSA are known to increase several-fold above plasma levels in various organs under acute and chronic uremic conditions (21,22) though GAA levels decrease (6,19).…”
Section: Discussionmentioning
confidence: 99%
“…Thus (about 120nM) (19). However, the levels of MG and GSA are known to increase several-fold above plasma levels in various organs under acute and chronic uremic conditions (21,22) though GAA levels decrease (6,19).…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of MG have been investigated since Giovanetti's group reported that MG accumulates in the serum of uremic patients as a uremic toxin. [14] Ozasa et al [15] reported that MG and CTL are present at similar levels in the serum of uremic rats. In humans, however, conversion of CTL to MG is poor, and MG can be detected as a minor Cr metabolite derived by reactive oxygen species.…”
Section: Discussionmentioning
confidence: 98%
“…(less than 500 daltons) are known to accumulate in patients with renal failure and characterize the uremic state. Methylguanidine (MG) is one such substance and is suspected to be a uremic toxin (GIOVANNETTI et al, 1973). It is unlikely, however, that MG was involved in the depressive effect of the low M.W.…”
Section: Discussionmentioning
confidence: 99%